Structural characteristics of samarium oxynitride on silicon substrate - Goh, K.H.; Haseeb, A.S. Md. Abdul; Wong, Y.H. (Elsevier, 2017)
Thermal oxynitridation of 20 nm sputtered pure samarium metal film on silicon substrates were carried out in nitrous oxide gas ambient at various temperatures (600–900 °C) for 15 min. Influences of the oxynitridation temperature on the structural and chemical properties of the SmxOyNz films had been investigated. The crystallinity of the SmxOyNz film and existence of the interfacial layer (SmaSibOcNd) had been evaluated by X-ray diffraction (XRD), Fourier transform infrared (FTIR), and Raman analysis. Crystallite size and microstrain of Sm2O3 were estimated by the Williamson-Hall (W-H) plot analysis. The calculated crystallite size of the Sm2O3 from Scherrer equation were compared with the calculated values from the W-H plot. The SmxOyNz film composed of Sm–O and Sm–N phases and its interfacial layer composed of mixed Sm–O, Sm–N, Sm–Si–O, and Si–N phases were observed by X-ray photoelectron spectrometer (XPS). The amount of Sm–O and Sm–N bonds at/near to the surface was higher than those at interfacial layer. High resolution transmission electron microscopy (HRTEM) attached with the energy dispersive X-ray (EDX) spectroscopy analysis was carried out to investigate the cross sectional morphology and the chemical distribution of selected regions. A physical model related to the polycrystalline structure of the SmxOyNz film and the amorphous structure of interfacial layer had been suggested and explained. Supportive results related to model were obtained by the FTIR, XRD, Raman, EDX, and HRTEM analysis. For 800 °C and 900 °C samples, the significant changes in the thickness of interfacial layer may also due to huge amount of NO produced during decomposition of N2O gas at 1000 K and above. No silicon dioxide or samarium silicide were formed between samarium oxynitride and Si substrate.